Periodontitis prevalence in adults ≥ 65 years of age, in the USA. Issue 1 (October 2016) - Eke, Paul I.; Wei, Liang; Borgnakke, Wenche S.; Thornton‐Evans, Gina; Zhang, Xingyou; Lu, Hua; McGuire, Lisa C.; Genco, Robert J.
Abstract: The older adult population is growing rapidly in the USA and it is expected that by 2040 the number of adults ≥ 65 years of age will have increased by about 50%. With the growth of this subpopulation, oral health status, and periodontal status in particular, becomes important in the quest to maintain an adequate quality of life. Poor oral health can have a major impact, leading to tooth loss, pain and discomfort, and may prevent older adults from chewing food properly, often leading to poor nutrition. Periodontitis is monitored in the USA at the national level as part of the Healthy People 2020 initiative. In this report, we provide estimates of the overall burden of periodontitis among adults ≥ 65 years of age and after stratification according to sociodemographic factors, modifiable risk factors (such as smoking status), the presence of other systemic conditions (such as diabetes) and access to dental care. We also estimated the burden of periodontitis within this age group at the state and local levels. Data from the National Health and Nutrition Examination Survey 2009/2010 and 2011/2012 cycles were analyzed. Periodontal measures from both survey cycles were based on a full‐mouth periodontal examination. Nineteen per cent of adults in this subpopulation were edentulous. The mean age was 73 years, 7% were current smokers, 8% lived below the 100% Federal Poverty Level and < 40% had seen a dentist in the past year. Almost two‐thirds (62.3%) had one or more sites with ≥ 5 mm of clinical attachment loss and almost half had at least one site with probing pocket depth of ≥ 4 mm. We estimated the lowest prevalence of periodontitis in Utah (62.3%) and New Hampshire (62.6%) and the highest in New Mexico, Hawaii, and the District of Columbia each with a prevalence of higher than 70%. Overall, periodontitis is highly prevalent in this subpopulation, with two‐thirds of dentate older adults affected at any geographic level. These findings provide an opportunity to determine how the overall health‐care management of older adults should consider the improvement of their oral health conditions. Many older adults do not have dental insurance and are also likely to have some chronic conditions, which can adversely affect their oral health.